Food waste warriors: Indonesian communities engage through workshops and social media education - Audrey, Monica; Rukmini, Elisabeth (Intelektual Pustaka Media Utama, 2024)
Food waste is food appropriate for human consumption but discarded in the retail or consumption process. In 2022, food waste accounts for 40.9% of Indonesia’s waste composition. Therefore, food waste community education is critical for reducing food waste. Community education can reach the young generation through workshops and social media. This research aims to evaluate various workshops and social media content in educating teenagers about food waste through community. The PRISMA guidelines become the foundation as a contribution to Sustainable Development Goals. We utilized databases such as EBSCO Host, SAGE, Taylor & Francis, and Wiley Online Library to search for relevant studies. This study’s approach is normative research including secondary data, comprehensive literature review such as workshops, social media, and food waste education journals in Indonesia. This systematic review examines food waste education content of workshops and social media in Indonesia also further content recommendations. This systematic review collected 52 papers, including journals and proceedings. The community education content in Indonesia focuses on recycling with 28.57%. Seminars/online campaigns dominate the education form with sustainable development goals (SDGs) achieved: climate action and zero hunger. This systematic review showed that it is essential to add actions toward food waste in the form of actual activities.